2017
DOI: 10.1038/nprot.2017.116
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing endocytic recycling and trafficking in live neurons by subdiffractional tracking of internalized molecules

Abstract: Our understanding of endocytic pathway dynamics is restricted by the diffraction limit of light microscopy. Although super-resolution techniques can overcome this issue, highly crowded cellular environments, such as nerve terminals, can also dramatically limit the tracking of multiple endocytic vesicles such as synaptic vesicles (SVs), which in turn restricts the analytical dissection of their discrete diffusional and transport states. We recently introduced a pulse-chase technique for subdiffractional trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 101 publications
2
74
0
Order By: Relevance
“…By applying super-resolution imaging approaches to study their dynamic nanoscale organization and vesicle dynamics (Joensuu et al, 2017;Joensuu et al, 2016), a more comprehensive picture of the dynamics of the exocytic molecular machinery will be developed, thereby revealing the principles that govern regulated exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…By applying super-resolution imaging approaches to study their dynamic nanoscale organization and vesicle dynamics (Joensuu et al, 2017;Joensuu et al, 2016), a more comprehensive picture of the dynamics of the exocytic molecular machinery will be developed, thereby revealing the principles that govern regulated exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In both situations, the glass surfaces were coated with poly-L-lysine (Sigma-Aldrich). Primary neuronal culture was performed as described previously (Joensuu et al, 2017). Briefly, the dissected hippocampi were digested with 0.25% trypsin-EDTA and DNase I for 20 min at 37°C, followed by mechanical trituration.…”
Section: Methodsmentioning
confidence: 99%
“…1c). This was followed by a thorough wash in culture medium to remove the excess fluorescent probe and confocal time-lapse imaging and automatic tracing of the fluorescently tagged cargoes as previously described (Joensuu et al, 2017; Wang et al, 2016; Wang et al, 2015). To investigate different stages of axonal trafficking, live-imaging was performed in two distinct axonal regions: (1) the axon shafts adjacent to the soma chamber (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we examined the diameter of axons in the presence or absence of cargoes at the ultrastructural level. In order to eliminate confounding factors related to the analysis of dendrites, experiments were only performed on axonal bundles formed within the channels of microfluidic devices (Joensuu et al, 2017; Wang et al, 2016; Wang et al, 2015), as shown in Fig. 2a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation